2021
DOI: 10.1080/17482631.2021.1978373
|View full text |Cite
|
Sign up to set email alerts
|

Understanding patient experiences in a motivational interviewing intervention to improve whole-person lifestyle among individuals with hypertension or type 2 diabetes: a qualitative focus group study

Abstract: McManus (2021) Understanding patient experiences in a motivational interviewing intervention to improve whole-person lifestyle among individuals with hypertension or type 2 diabetes: a qualitative focus group study,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…This is in line with the findings of a systematic review on the effect of MI on lifestyle modification that found moderate evidence of the beneficial effect of MI on promoting physical activity participation. 34 An intervention study using Telephone MI conducted among the Dutch population found a significant relationship between the percentage of MI adherent expressions and change in the level of PA from baseline to 47-week follow-up, with a small effect size (p<0.05). 37…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is in line with the findings of a systematic review on the effect of MI on lifestyle modification that found moderate evidence of the beneficial effect of MI on promoting physical activity participation. 34 An intervention study using Telephone MI conducted among the Dutch population found a significant relationship between the percentage of MI adherent expressions and change in the level of PA from baseline to 47-week follow-up, with a small effect size (p<0.05). 37…”
Section: Discussionmentioning
confidence: 99%
“…Yet another systematic review discovered moderate evidence supporting the positive impact of motivational interviewing on smoking cessation. 34…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are numerous reports stating that mental health should be a key element of lifestyle interventions,63,64 many participants in this review still report they cannot do it on their own and need more psychological guidance. Program staff should therefore be trained to give psychological guidance, such as motivational interviewing,65 and inform the GP of the issues. As lifestyle interventions are multicomponent programs and multidisciplinary, it might not be feasible to guarantee that the HCPs involved can help participants with mental health conditions.…”
mentioning
confidence: 99%